The digitally disadvantaged: Access to digital communication technologies among first year students at a rural South African University - Oyedemi, Toks; Mogano, Saki (Pretoria: Unisa Press and Routledge, 2018)
Considering the importance of digital skills in university education, this article reports on a study which examined access to technology among first year students at a rural South African university. The study focused on the digital readiness of students prior to their admission to the university, since many universities provide access to computers and the internet. The survey of 156 first year students revealed that 73 per cent of the students had no access to computers at their high schools and 82 per cent of students from rural high schools had no computer access and internet at their schools. Most students from rural areas used a computer for the first time when they were 19 years and older. Many students gained access to computers and the internet for the first time at the university. As a result, they enter the university digitally disadvantaged. Solutions that involve initiatives to provide access to technology are required in addition to digital literacy for educators at high schools.
Keywords: Digitally disadvantaged; Digital inequality; Rural university